Solar energy in the Apaquí River Basin as a basis for the formulation of sustainable development projects, Carchi-Ecuador - Ruiz Pomasqui, Consuelo del Pilar; Mora Trujillo, Germán Alfredo; Heredia Enríquez, Nelson Germán (Tierra Infinita, 2019)
The objective of the present investigation was to assess the energy and temporal distribution of the sun heliophany that resides in the Apaquí river basin for the purpose of generating electricity, by assessing irradiance with application of geographic information systems (GIS). The analysis was to obtain reliable and accurate information from meteorological stations in the Apaquí River basin. The solar data published in the INAMHI meteorological yearbooks were compared with satellite information. In the study, the average, monthly and annual solar radiation was determined, with information of 25 years. Likewise, the solar map of the basin under study was generated that allowed the spatial location and the available power of the sun to be used in power generation projects with photovoltaic systems. The solar map also allows us to examine the distribution, temporality and intensity of solar radiation. In this way, the research indicates that the maximum irradiance occurs in the months of July, August and September, in the dry season in Ecuador with power of 14.84 KJ / m2 / day. The low irradiance of the Apaquí River basin was registered in January, February and March with a power of 13.83 KJ / m2 / day, fundamental data that support the execution of power generation projects using the radiant energy of the sun with zero CO2 emissions, which helps to reduce the effects of climate change. Keywords: Irradiance, intensity, solar map, heliophany